Pelaksanaan Sistem Rujukan Eksternal Pasien di Puskesmas Kota Mataram - Hadi, Irwan; Halid, Sopian; Supriyadi, Supriyadi; Idris, Baiq Nurainun Apriani; Istiana, Dian (Jurnal Ilmiah STIKES Yarsi Mataram, 2020)
Implementation of Referral System is one of the instruments to measure the quality of health services to the public. Satisfaction feeling of services quality presently still less in public, especially in making external referrals. The aimed of this research was to determine the implementation of the external referral system for patients in Matarampublic health center. The design used in this research was descriptive design. The samplesused in this researchwere 76 people, they were takenby purposive sampling technique. The research instrumentsin this research used an observation sheet and a questionnaire. Implementation of the external referral system based on Standard Operating Procedure with 72 (94.7%) respondents and the implementation of the external referral system out of Standard Operating Procedure with 4 (5.3%) respondents. The external referral system in clinical procedures shows that the implementation of the external referral system based on Standard Operating Procedure were 65 (85.5%) and the implementation of the external referral system out of Standard Operating Procedure were 11 (14.5%) respondents. The administrative procedure shows that the implementation of the patient's external referral system based on Standard Operating Procedure were 37 (48.7%) and the implementation of the external patient referral system out of Standard Operating Procedure. It is expected that the quality of health services will improve using the standard operating procedures that have been established